New Tools to Study Astrocyte Ca2+ Signal Dynamics in Brain Networks In Vivo - Losi, Gabriele; Mariotti, Letizia; Sessolo, Michele; Carmignoto, Giorgio (Frontiers in Cellular Neuroscience, 2017)
Sensory information processing is a fundamental operation in the brain that is based on dynamic interactions between different neuronal populations. Astrocytes, a type of glial cells, have been proposed to represent active elements of brain microcircuits that, through dynamic interactions with neurons, provide a modulatory control of neuronal network activity. Specifically, astrocytes in different brain regions have been described to respond to neuronal signals with intracellular Ca2+ elevations that represent a key step in the functional recruitment of astrocytes to specific brain circuits. Accumulating evidence shows that Ca2+ elevations regulate the release of gliotransmitters that, in turn, modulate synaptic transmission and neuronal excitability. Recent studies also provided new insights into the spatial and temporal features of astrocytic Ca2+ elevations revealing a surprising complexity of Ca2+ signal dynamics in astrocytes. Here we discuss how recently developed experimental tools such as the genetically encoded Ca2+ indicators (GECI), optogenetics and chemogenetics can be applied to the study of astrocytic Ca2+ signals in the living brain.